Introduction to “Criminal justice and globalization at the new millennium” - Weiss, Robert P. (Social justice, 2000)
Part of a special issue on criminal justice at the new millennium. The writer introduces the articles in this special issue. He indicates that neoliberal globalization is the guiding political economy of the new millennium. He also contends that neoliberalism has had an impact on criminal justice almost everywhere because of the free-market paradigm that precludes the requirement for any program of social justice. He also discusses the implications for those who lose out in the process of globalization.